Прогнозування динамічних процесів на основі математичних моделей часових рядів із різнотемповою дискретизацією - Romanenko, V. D. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Theoretical propositions concerning multirate system design for prognostication of dynamic coordinates of one- and multidimensional processes under discretization of input disturbances with small periods of sampling and output coordinates with large periods of sampling are considered. Dynamics of stationary processes is represented by autoregression and sliding mean models and those of nonstationary ones by autoregression and integrated sliding mean models with multirate discretization.